EFFECT OF FOREST COVER ON SOIL CHARACTERISTICS AT THE FINCA EXPERIMENTAL INTERDISCIPLINARIA DE MODELOS AGROECOLÓGICOS: A CASE STUDY - Mora-Chacón, Josué; Nakajima, Shiori; A. Rojas, Pedro; Rojas, Carlos (InterSedes, 2019)
Soil management is essential in the context of climate change adaptation, but baseline information is first required for its management, use and conservation. This project aimed to address the poor documentation of the soil in the forest section of the Finca Experimental Interdisciplinaria de Modelos Agroecológicos in Turrialba, Costa Rica. The aim of this study was to analyze the effect of land use on physicochemical characteristics of the soil to contrast the processes associated with forest management and evaluate the temporal effect of zonification on soil characteristics. A series of biological variables were also determined to evaluate response uniformity within the forest. For all the studied area, soil texture was classified as medium and coarse and chemical fertility was medium to high without major differences among land use sections. However, color, apparent density (0.6-1.4 g/cm3), porosity (48.2-77.7 %) and infiltration velocity (552-3405 mm/day) were influenced by soil texture and land use. Soil respiration had a high average of 46.33 µg C-CO2/gh and no differences in biological variables were observed within the forest. The information obtained in this study demonstrated that forest cover has had a stronger impact on structural variables in relation with other land use types. The forest, however, seemed to have developed as a functional homogeneous unit.